"As Long as They Have Talent": Organizational Barriers to Black Ballet. Issue 3 (2nd September 2018) - Erin Lauren, Brown
Abstract: This article investigates the relative absence of African American ballet dancers and the field's slow integration. It counters scarcity theories—not enough interest, money, or opportunities—demonstrating a demand for ballet in postwar black communities. Further, it argues that postwar funding, private sources from the Ford Foundation and national programs under the National Endowment for the Arts, unintentionally strengthened boundaries between white and black dancers through racialized funding, as evidenced in support patterns for the Dance Theatre of Harlem. Instead of normalizing mixed-race companies or questioning racial limits, funding bolstered old stereotypes regarding "looks" and choreographers' preferences as aesthetic law.